Stable walking in a biped robot with force-feedback-induced center-of-mass regulation. (2nd October 2016) - Chen, Jing-Yi; Lu, Jau-Ching; Chen, Ching-Pei; Lin, Pei-Chun
Abstract: We report on a novel ZMP feedback control strategy which regulates the center of mass trajectory of a robot based on the measured zero-moment point (ZMP). Based on the trajectory generated by preview control and the linear inverted pendulum model, the controller has an extra model-based control input which is driven by the center-of-mass (CoM) acceleration, which provides sensitive response to disturbance. Thus, the robot motion is balanced between the long-term nominal CoM/ZMP trajectory tracking and the short-term trajectory modification for disturbance rejection. In addition, the controller has two layers of adjustment strategy. When the disturbance is small, the robot is regulated by merely adjusting its CoM trajectory. In contrast, when the disturbance is large, the foot position of the robot is simultaneously changed to provide a more effective response with characteristics of larger intrinsic stability. The performance of the control strategy is also experimentally evaluated using a child-size biped robot.